2019
DOI: 10.1098/rsif.2018.0641
|View full text |Cite
|
Sign up to set email alerts
|

Wing morphing allows gulls to modulate static pitch stability during gliding

Abstract: A gliding bird's ability to stabilize its flight path is as critical as its ability to produce sufficient lift. In flight, birds often morph the shape of their wings, but the consequences of avian wing morphing on flight stability are not well understood. Here, we investigate how morphing the gull elbow joint in gliding flight affects their static pitch stability. First, we combined observations of freely gliding gulls and measurements from gull wing cadavers to identify the wing configurations used du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 26 publications
0
77
0
Order By: Relevance
“…Birds can maintain pitch stability (pitch moment curve with a negative slope) and balance (positive lift when in trim) during gliding flight solely through the geometry of their main wing (14,24). This aerodynamic characteristic improves the versatility of the bird's horizontal tail (for example, to generate lift) compared with traditional aircraft, where the tail acts solely as a pitch stabilizer and elevator (21).…”
Section: Morphing Wingmentioning
confidence: 99%
See 1 more Smart Citation
“…Birds can maintain pitch stability (pitch moment curve with a negative slope) and balance (positive lift when in trim) during gliding flight solely through the geometry of their main wing (14,24). This aerodynamic characteristic improves the versatility of the bird's horizontal tail (for example, to generate lift) compared with traditional aircraft, where the tail acts solely as a pitch stabilizer and elevator (21).…”
Section: Morphing Wingmentioning
confidence: 99%
“…The relatively short bodies of birds, which resemble more flying wings than traditional aircrafts, and their lightweight wings contribute to lower inherent inertia, which further enhances agility (21)(22)(23). Furthermore, in aggressive flight, birds actively reduce longitudinal stability by sweeping the main wings forward and minimizing the tail's surface (24,25). However, in fast cruise flight ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Wings dramatically morph during flapping flight (Wolf and Konrath, 2015), but it is unclear how many active degrees of freedom are available for controlling morphing. Bird wings are highly coupled; the internal structure of a bird’s wing acts as a linkage, where the bones and feathers generally move together in prescribed ways (Matloff et al, 2020; Harvey et al, 2019), and much of the obvious shape change is controlled by a single degree of freedom. However, there is a theoretical capacity for near-infinite degrees of freedom in wing shape due to anatomical complexity.…”
Section: Introductionmentioning
confidence: 99%
“…By observing the wing shape change of raptor size birds, such as steppe eagle, swift, gull, albatross, etc, biologists have found that the arm-wing (inboard portion containing the secondary feathers) moves forward with the wrist joint, while the hand-wing (outer portion of wing consisting of the primary feathers) is swept to the rear. The influence of this morphing mode on aerodynamic characteristics, static stability and efficiency of mission execution has been widely studied [14]- [17]. Asymmetric morphing modes are utilized by birds for generating moments in maneuver flight.…”
Section: Velocity Potentialmentioning
confidence: 99%
“…Through the observation of raptor size birds, the actual working part of their wings can be separated into arm-wing and hand-wing part [14]- [17], as shown in Figure 2. The two parts have an approximately equal span and can change the sweep angles in opposite directions.…”
Section: Aerodynamic Analysismentioning
confidence: 99%